2011
DOI: 10.1016/j.envres.2011.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Phthalate exposure associated with self-reported diabetes among Mexican women

Abstract: Background Phthalates are ubiquitous industrial chemicals used as plasticizers in plastics made of polyvinyl chloride (PVC) to confer flexibility and durability. They are also present in products used for personal-care, industry and in medical devices. Phthalates have been associated with several adverse health effects, and recently it has been proposed that exposure to phthalates, could have an effect on metabolic homeostasis. This exploratory cross-sectional study evaluated the possible association between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 30 publications
5
84
0
Order By: Relevance
“…Moreover, BPA has been shown to be associated with altered insulin release in human tissue samples (Soriano et al, 2012). Positive associations between phthalates and type 2 diabetes were found in the NHSII (Sun et al, 2014) and NHANES (James-Todd et al, 2012) cohorts, as well as in cross-sectional studies from Mexico (Svensson et al, 2011) and Sweden (Lind et al, 2012). Biological evidence supports a possible role for phthalates in the development of diabetes, principally through activation of PPARs, which in turn affect adipogenesis, lipid storage and the control of insulin sensitivity (Casals-Casas and Desvergne, 2011;Hurst and Waxman, 2003).…”
Section: Figmentioning
confidence: 92%
“…Moreover, BPA has been shown to be associated with altered insulin release in human tissue samples (Soriano et al, 2012). Positive associations between phthalates and type 2 diabetes were found in the NHSII (Sun et al, 2014) and NHANES (James-Todd et al, 2012) cohorts, as well as in cross-sectional studies from Mexico (Svensson et al, 2011) and Sweden (Lind et al, 2012). Biological evidence supports a possible role for phthalates in the development of diabetes, principally through activation of PPARs, which in turn affect adipogenesis, lipid storage and the control of insulin sensitivity (Casals-Casas and Desvergne, 2011;Hurst and Waxman, 2003).…”
Section: Figmentioning
confidence: 92%
“…Despite concerns about the toxicity of PhE for humans, the cytotoxic properties of these materials have not been clearly characterized [3,4]. The application of these substances is widespread globally, and their metabolites are therefore widely detectable in body's fluids such as serum and urine among populations of different societies [5][6][7]. PhE can be absorbed to human body through inhalation, oral ingestion, skin absorption, and via the parenteral routes [8][9][10].…”
Section: Introductionmentioning
confidence: 98%
“…In this study, we observed a decrease in insulin and elevated fasting blood glucose level along with impaired glucose and insulin tolerances and reduced glycogen concentrations at PND60 of F 1 offspring exposed to DEHP. Results from previous studies have indicated that DEHP impairs blood glucose regulation (Gayathri et al 2004, Stahlhut et al 2007, Srinivasan et al 2011, Svensson et al 2011 in rats and humans. In addition, we found significantly lower lean body weight with higher fat mass at PND60.…”
Section: Discussionmentioning
confidence: 99%